Rising above financial storms top advice from Asia's no.1 investment guru - Chong Koay, Tan (Percetakan Zanders Sdn Bhd, 2015)
This book is about equity investing. It provides many gems of wisdom on how to be a succesful investor, even amid financial crises. Here, author Dr. Tan Chong Koay, founder of Pheim Malaysia and Pheim Singapore, sets out his investing philosophy, which is based on his many decades of investing in emerging as well as developed markets. Dr. Tan's view is that successful investing need not be the exclusive domain of a few. The objective of this book is to help the reader invest in equities, particularly in the Asean region, taking into consideration the volatile nature of emerging markets. Most can invest successfully by following a set of rules, Dr. Tan says. To illustratem he shows the thinking behind some of the stocks he picked and some of the discipline in play that has enabled the funds he managed to consistently outperform both the relevant benchmark indices and competitors in the long run. It's not a pure "how-to" book at it also details Dr. Tan's personal journey; it's not about just the many successes but also the heartbreaks and lessons learnt.